Appyling Maslow's Hierarchy Theory - Bennett, Marlyn; Shangreaux, Corbin (First Peoples Child & Family Review, 2005)
This paper evolved from the outcome of a feedback meeting held between the principle researchers of Cycle II of the Canadian Incidence Study of Reported Child Abuse and Neglect (CIS), the Public Health Agency of Canada (PHAC) and a number of representatives of the First Nations Child and Family Service Agencies (FNCFS Agencies) which participated in Cycle II of the CIS (CIS-2003) and numerous Research Assistants tasked with collecting information from the FNCFS Agencies. The authors present a profile of the historical and contemporary experience of Aboriginal children and families who come into contact with the child welfare system and include a discussion on some of the findings from two analyses that have been conducted on the data from the 1998 Canadian Incident Study of Reported Child Abuse and Neglect (CIS-1998). An overview of the challenges as well as the positive aspects of the study from the perspectives of the FNCFS Agencies and the Research Assistances is included along with an examination as to why research may not figure prominently among the service priorities of FNCFS Agencies. The strengths of challenges of participating in CIS-2003 provide rich insight into the perspectives of the Research Assistants and FNCFS Agencies who participated in this national study. The paper concludes with recommendations by the FNCFS Agencies and the Research Assistants on how to improve the data collection process with FNCFS Agencies for future Cycles of the Canadian Incident Study of Reported Child Abuse and Neglect.